Comparison of 532 nm Micropulse Green Laser versus Continuous-Wave 532 nm Green Laser in Chronic Central Serous Chorioretinopathy: Long-Term Follow-Up. (31st January 2020) - Piasecka, Katarzyna; Gozdek, Piotr; Maroszyński, Mariusz; Odrobina, Dominik
Abstract : The aim of this study was to analyze the efficacy of micropulse laser treatment (MLT) compared with the continuous-wave laser (CL) in treating eyes with chronic central serous chorioretinopathy (CSC) in a 12-month follow-up study. Methods : A retrospective observational study included 51 eyes with chronic CSC; 35 eyes were treated with MLT (Group A), and 16 eyes were treated with CL (Group B). We analyzed the best corrected visual acuity (BCVA) and retinal microstructural changes in spectral optical coherence tomography before the treatment, one and twelve months after the laser procedure. Results : The final mean BCVA was 0.89 ± 0.13 in Group A and 0.71 ± 0.17 in Group B. Photoreceptor length decreased significantly in both groups and amounted 61.2 μ m in Group A and 42.9 μ m in Group B one year after the treatment. Complete absorption of subretinal fluid twelve months after the laser procedure was noted in 74.3% eyes in Group A and in 87.5% eyes in group B. Hyper-reflective subretinal deposits were observed in 10/35 eyes in Group A but in 15/16 eyes in Group B on the final follow-up visit. Conclusion . MLT-treated patients showed better functional and microstructural results than patients treated with CL.